2014
DOI: 10.2478/acph-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Use of compounded dispersing media for extemporaneous pediatric syrups with candesartan cilexetil and valsartan

Abstract: Available tablets or capsules for adults are often used to prepare extemporaneously formulated medicines appropriate for children. The most acceptable drug forms in pediatric population are oral liquids and pharmacists use commercial dispersing media to compound syrups from an active substance or from tablets available on the market. In many countries ready-to-use dispersing media are not available or refunded, but pharmacists can use other compounded media, providing their compatibility and stability are prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…sorbitoli (70%), mucillago methylcellulosae (1%), mucillago gummi arabici (1%), mucillago gummi xanthani (1%), mucillago NaCMC (1%). [11][12][13][14][15][16][17] The full list of excipients and the combinations of them are summarized in Table 1.…”
Section: Composition and Preparation Of Nitrofurantoin Model Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…sorbitoli (70%), mucillago methylcellulosae (1%), mucillago gummi arabici (1%), mucillago gummi xanthani (1%), mucillago NaCMC (1%). [11][12][13][14][15][16][17] The full list of excipients and the combinations of them are summarized in Table 1.…”
Section: Composition and Preparation Of Nitrofurantoin Model Vehiclesmentioning
confidence: 99%
“…The found value is corresponding to those published in different official sources. [9][10][11][12][13][14][15][16][17][18] At this wavelength, the standard equation is:…”
Section: Preliminary Uv-vis Spectrophotometrical Determination Of Con...mentioning
confidence: 99%
“…[12,13] Due to the legal regulations in some countries, the final cost of prepared extemporaneous syrups is high due to unregistered components for pharmaceutical use. [13,14] In this study, we focused on the cost analysis of antihypertensive pediatric formulations in Saudi Arabia. The rationale behind the New Vision of Saudi Arabia 2030 is to aim at privatization, determine the cost and the profits of these extemporaneous formulations and to compare the prices of different formulations and chose the cheapest one in preparing these formulations in the future.…”
Section: S3mentioning
confidence: 99%
“…Ferreira et al prepared a SDZ formulation using SyrSpend ® SF PH4 and demonstrated stability for 120 days. However, these vehicles are not available in many countries and the final cost of the prepared extemporaneous suspensions is high; moreover, commercial suspending media are not registered for pharmaceutical use . Thus, it is indispensable to assess the stability of SDZ in suspensions, which could be prepared extemporaneously, easily and cheaply.…”
Section: Introductionmentioning
confidence: 99%